Perancangan UI/UX Aplikasi Mobile Monitoring Barang Rusak dan Retur di Mencirim Swalayan dengan Metode User-Centered Design - Al Yafi Ramadhan; Ruly Dwi Arista; Heni Wulandari (Jurnal Nasional Teknologi Komputer, 2026)
Operational efficiency in the retail business heavily relies on accurate inventory management systems, particularly in handling damaged goods and return processes. Mencirim Swalayan currently faces challenges due to manual recording procedures that trigger data error risks and response delays. This research aims to design the User Interface (UI) and User Experience (UX) of a mobile monitoring application tailored to operational needs using the User-Centered Design (UCD) approach. The UCD method is employed to ensure the design focuses on end-user needs through four main stages: understanding the context of use, specifying user requirements, designing solutions, and evaluation. The result of this study is an application design that integrates barcode scanning, physical photo documentation, and a real-time return status monitoring dashboard. Design evaluation was conducted using the System Usability Scale (SUS) instrument with 10 respondents, yielding an average score of 79.5. These results indicate that the application has a usability level in the "Good" category with an "Acceptable" rating, making it feasible for implementation to improve data accuracy and staff work efficiency at Mencirim Swalayan.